2004
DOI: 10.1182/blood-2003-12-4347
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of the AF1q gene, an MLL fusion partner, is an independent adverse prognostic factor in pediatric acute myeloid leukemia

Abstract: The AF1q gene, a mixed-lineage leukemia fusion partner, is highly expressed in hematopoietic progenitor cells but has low expression in differentiated cells. We determined the expression of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 26 publications
5
57
2
Order By: Relevance
“…27 In another study, in 64 unselected pediatric AML samples, high AF1q expression was independently associated with poor survival. 28 Whether MLL-AF1q causes different expression levels of AF1q remains unknown; hence, further studies should address the underlying biology. Given the excellent outcome of this rare subgroup of patients, we suggest that direct screening for this translocation be incorporated in future pediatric AML treatment protocols and that patients with MLLAF1q should be allocated to the low-risk group (or treatment arm) of these protocols.…”
Section: Discussionmentioning
confidence: 99%
“…27 In another study, in 64 unselected pediatric AML samples, high AF1q expression was independently associated with poor survival. 28 Whether MLL-AF1q causes different expression levels of AF1q remains unknown; hence, further studies should address the underlying biology. Given the excellent outcome of this rare subgroup of patients, we suggest that direct screening for this translocation be incorporated in future pediatric AML treatment protocols and that patients with MLLAF1q should be allocated to the low-risk group (or treatment arm) of these protocols.…”
Section: Discussionmentioning
confidence: 99%
“…However, 8 out of 24 overexpressed genes did not belong to any of the above-mentioned functional groups. Although two genes, PDZK1 and MLLT11, were clearly relevant to cancer as both have been proposed as a candidate oncogene in diverse haematological malignancies (Busson-Le Coniat et al, 1999;Inoue et al, 2004;Tse et al, 2004), six were more difficult to relate to cancer. Three corresponded to genetic determinants of genetic syndromes (MTMR, DISC1, MTX1) and the three others bore functions with no obvious link to cancer (NENF, ENSA, TARBP1).…”
Section: Discussionmentioning
confidence: 99%
“…In cell lines overexpression of MLLT11 was associated with enhanced doxorubicininduced apoptosis, 78 whereas another study showed that high MLLT11 expression in AML was independently associated with poor survival. 79 By contrast, the t(10;11)(p12;q23) and t(6;11) (q27;q23) subgroup have poor prognosis, with a 5y-pEFS of 31 and 11% and a 5y-pOS of 45 and 22%, respectively. Also, adult AML patients with a t(6;11)(q27;q23) have a poor outcome.…”
Section: Mll-rearrangedmentioning
confidence: 98%